MAPPING PHONOLOGICAL CHANGE: A GEOLINGUISTIC STUDY OF /W/ AND /B/ VARIATION IN BAHASA JAWA CIREBON - Juwintan; Eri Kurniawan; R. Dian Dia-an Muniroh (University of Kuningan, 2025)
Phonological difference between geographical areas is a primary topic for dialectology and sociolinguistics, especially in multilingual settings like Indonesia. Previous studies of Cirebon Javanese have been mostly concerned with lexical matters and general dialect groupings, whereas the more detailed phonemic differences and their geographical dynamics are understudied. Previous studies of Cirebon Javanese have been mostly concerned with lexical matters and general dialect groupings, whereas the more detailed phonemic differences and their geographical dynamics are understudied. This research is intended to describe the spatial distribution of consonantal phonemes /w/ and /b/ in Cirebon Javanese and identify points of conservatism and innovation. This research applied a descriptive qualitative research design, with data obtained from 534 respondents from 267 villages in four distinct areas (North, East, Central, and Northwest Cirebon). The five key lexical items that showed variation between /w/ and /b/ were examined through structured interviews, phonological coding, and geospatial analysis with the help of QGIS. The /w/ phoneme was predominantly present in the Northern and Eastern regions, with archaic linguistic features. The /b/ phoneme was discovered to be more prevalent in Central Cirebon, with phonological innovation as a result of urbanization and contact with Standard Indonesian. Also, transitional zones with merged forms were discovered in Northwest Cirebon. The geographical, social, and contact factors influence the phonological variation of Cirebon Javanese. This research underscores the need to incorporate spatial technologies into sociophonological investigation and informs a more nuanced understanding of dialect change in multilingual settings. Theoretically, it advances micro-level geolinguistic analysis; practically, it aids dialect documentation and preservation.